Attitude about mental illness of health care providers and community leaders in rural Haryana, North India - Salve, Harshal Ramesh; Babu, Surendra; Rai, Sanjay K; Sagar, Rajesh; Kant, Shashi (Indian Journal of Community Health, 2014)
Background: Attitude about mental illness determines health seeking of the people. Success of National Mental Health Programme (NMHP) is dependent on attitude about mental illness of various stakeholders in the programme. Material & Methods: A community based cross-sectional study was carried out in Ballabgarh block of Faridabad district in Haryana. We aimed to study attitude about mental illness of various stakeholders of health care providers (HCP), community leaders in rural area of Haryana, north India. Study area consisting of five Primary Health Centers (PHCs) serving 2,12,000 rural population. All HCP working at PHCs, Accredited Social Health Activist (ASHA) and community leaders in study area were approached for participation. Hindi version of Opinion about Mental illness Scale for Chinese Community (OMICC) was used to study attitude. Results: In total, 467 participants were participated in the study. Of which, HCP, ASHAs and community leaders were 81 (17.4%), 145 (31.0%) and 241 (51.6%) respectively. Community members reported socially restrictive, pessimistic and stereotyping attitude towards mentally ill person. ASHA and HCP reported stereotyping attitude about person with mental illness. None of the stakeholders reported stigmatizing attitude. Conclusion: Training programme focusing on spectrum of mental illness for HCP and ASHA working in rural area under NMHP programme is needed. Awareness generation of community leaders about bio-medical concept of mental illness is cornerstone of NMHP success in India.